Animal models of systemic lupus erythematosus and their applications in drug discovery. (4th May 2022) - Xin, Yue; Zhang, Bo; Zhao, Junpeng; Liu, Qianmei; Yin, Haoyuan; Lu, Qianjin
ABSTRACT: Introduction: Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease with substantial phenotypic heterogeneity. Currently, our understanding of the pathogenesis is still limited, and as a result, specific and efficacious therapies are lacking. Various mouse models have been established to serve as powerful tools that will promote a better understanding of the disease and the ability to test novel drugs before clinical application. Areas covered: The authors review the existing mouse models of SLE in terms of pathogenesis and manifestations, as well as their applications in drug discovery and development. The areas of focus include promising novel therapeutics that could benefit patients in the future and the contribution of mouse models used in preclinical studies. Expert opinion: Given the diversity of SLE mouse models with different characteristics, researchers must select a suitable model based on the mechanism involved. The use of multiple models is needed for drug testing studies to evaluate drug efficacy on different genetic backgrounds and other mechanisms to provide a reference for clinical trials.